EVALUATION OF EFFICACY AND SAFETY OF ORAL ANTICOAGULANTS IN PATIENTS WITH ATRIAL FIBRILLATION IN PROSPECTIVE FOLLOW-UP - M. V. Khruslov; M. A. Karpenko; T. V. Vavilova; T. A. Barbashina; A. S. Sorokina; E. V. Kovaleva; D. V. Eliseeva; N. V. Vasilievа; L. V. Safronova; I. V. Ponomareva; V. S. Kucherenko («REMEDIUM GROUP» Ltd., 2020)
PURPOSE. To evaluate the effectiveness and safety of warfarin therapy using a clinical laboratory model of centralized monitoring of international normalized relationships, and direct oral anticoagulants in patients with atrial fibrillation in real clinical practice.MATERIAL AND METHODS. In a non-interactive prospective study, 661 atrial fibrillation patients were prescribed oral anticoagulants to prevent cardioembolic complications. The study included patients older than 18 years of age, with creatinine clearance at least 50 ml/min. Рatients were divided into 4 groups: 1 group of 120 people who took warfarin was observed in the conditions of centralized monitoring the international normalized ratio (INR), group 2 - 112 people- was taking Rivaroxaban, group 3 - 106 people- was taking Dabigatran, group 4 - 98 people took Apixaban. Formed 4 groups of patients were comparable in age, concomitant diseases, risks of thromboembolic and hemorrhagic complications.The follow-up period was 2 years from the date of prescribing.RESULTS. In patients who were observed in the clinical laboratory model of centralized monitoring of INR, the TTR was 69.4%. The groups did not differ in the number of thromboembolic complications (p>0.05). Warfarin had an advantage in the amount of large bleeding - 0.9% versus 3.6% taking rivaroxaban and 3.8% taking dabigatran (p = 0.044 and p = 0.035, respectively) without statistical significance for apixaban.CONCLUSION. The ratio of efficacy and safety of warfarin therapy can be successfully maintained at a satisfactory level using a centralized monitoring system of international normalized relationships. It allows you to get comparable treatment results with warfarin and direct inhibitors of blood coagulation factors in real clinical practice.